2004
DOI: 10.1111/j.0959-9673.2004.0368.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress and apoptosis in acute puromycin aminonucleoside nephrosis

Abstract: Accumulating evidence demonstrates that oxidative stress is one of the underlying mechanisms to induce apoptosis in different biological systems. The aim of this study was to examine the simultaneous presence and correlation between oxidative stress events, apoptosis, apoptosis-associated proteins and monocyte/macrophage infiltration during the course of acute puromycin aminonucleoside nephrosis (PAN). To induce nephrosis, Sprague-Dawley rats were injected intraperitoneally with puromycin aminonucleoside and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 40 publications
5
29
0
Order By: Relevance
“…A recent study described that IGF-1 protected podocytes from etoposide-induced apoptosis and that Bad phosphorylation as well as the activation of the phosphatidylinositol 3Ј-kinase pathway were associated with the antiapoptotic effect (52). In this study, we showed that exposure of podocytes to PA increased levels of Bax, which is consistent with findings from previous in vivo studies in the PAN rat model of FSGS (48). Our data also showed that PA reduces the antiapoptotic protein Bcl-xL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study described that IGF-1 protected podocytes from etoposide-induced apoptosis and that Bad phosphorylation as well as the activation of the phosphatidylinositol 3Ј-kinase pathway were associated with the antiapoptotic effect (52). In this study, we showed that exposure of podocytes to PA increased levels of Bax, which is consistent with findings from previous in vivo studies in the PAN rat model of FSGS (48). Our data also showed that PA reduces the antiapoptotic protein Bcl-xL.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, dexamethasone completely suppressed the upregulation of p53 induced by PA. Taken together, these results suggest that PA-induced podocyte apoptosis is p53 dependent and that dexamethasone may protect podocytes from PA-induced podocytes by inhibiting p53. Previous studies showed that p53 is increased in PAN rats in vivo (48,49). We recently described an increase in p53 in podocytes in experimental membranous nephropathy (50).…”
Section: Discussionmentioning
confidence: 71%
“…M1 macrophages exhibit proinflammatory properties, whereas, M2 macrophages promote fibrogenesis and tissue remodeling. Studies have shown that inhibition of macrophage infiltration reduces proteinuria and structural injury in models including antiglomerular basement disease, puromycin aminonucleoside nephrosis, and Heymann nephritis (8,31,41). It has been suggested that macrophage inhibition is likely to be an effective therapeutic approach in CKD treatment.…”
mentioning
confidence: 99%
“…The PAN model has over the years become an experimental prototype of human minimal change disease and focal segmental glomerulosclerosis (39), and there is accumulating evidence that ROS generation and oxidative stress are main features of the pathogenesis of the glomerular barrier disruption induced by PAN (13,20,36,42,43,50). Hence, an increased production of ROS will activate TRPC6 Ca 2ϩ channels and intracellular Ca 2ϩ signaling (50) to increase glomerular permeability and to eventually produce DNA damage, cell cycle arrest, and thereby cell injury (32).…”
Section: Discussionmentioning
confidence: 99%